لال مسجد آپریشن پرروزنامہ ڈان اور روزنامہ جنگ میں شائع ہونے والی تفتیشی خبروں کا تحقیقی و تجزیاتی جائزہ - Aleem, Noureen; Khanum, Masroor (Journal of Mass Communication Department, Dept of Mass Communication, University of Karachi, 2019)
The laws and policies for journalism proposed by the East India Company were enforced since the advent of Pakistan. On the pretext of posing threat to state's sovereignty, the democratic and military governments in Pakistan made stern amendments to curb freedom of expression against the ruling party. This had put halt to the ongoing process of investigative reporting. To analyze the level of investigative reporting on the incident of Lal Masjid and the search operation, the topic of "content analysis of the investigative reports published in daily Jang and daily Dawn regarding the Lal Masjid operation" has been selected to analyze the role of investigative reporting in the same context. The study was carried out with the help of qualitative content analysis using the probability sampling technique. The conflict arose between the government of General (R) Pervez Musharraf and the administration of Lal Masjid when the construction of Sharaie Courts, rehabilitation of the demolished Masjids in Islamabad and the imposition of Shariah System in the surroundings of Lal Masjid was declared. Consequently the government tried to negotiate with the Lal Masjid administration which carried out no results. Hence, the operation took place on 4th July wiping out 70 people including 8 security workers